Struktur Konstruksi Wacana Sufisme - Zaprulkhan, Zaprulkhan (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2018)
Normatively, the structure of Sufi discourse construction comes from within the religion of Islam itself. According to Ibn Khaldun, Sufism comes from authentic Islamic law. The seeds originally came from the first generation of Muslims as the path of truth and guidance. Sufi approaches based on their consistency in the service of God, reluctant to worldly pleasures, abstain from the false delights, wealth, and position hunted by most humans, and busy solitude in worship to God. Therefore in Islam, there can be no spirituality without the aid of the Qur'an, which teaches man everything he can know or can learn, and which can lead people to the ideals that are the object of his creation. This article will elaborate the structure of the construction of Sufism discourse originating from Islam